2017
DOI: 10.1007/s00192-017-3468-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fellowship surgical training on operative time and patient morbidity during robotics-assisted sacrocolpopexy

Abstract: When an expert surgeon operated together with a fellow, operative time increased by 34 min without increasing prolapse recurrence or complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Increasingly, reconstructive and POP procedures are being performed by high-volume surgeons in general and those fellowship trained in female pelvic medicine and reconstructive surgery, with the former reflected in this cohort, where more than 75% of cases were performed by surgeons who perform more than 50 surgical procedures for POP per year 17–19 . Previous studies have suggested that both fellowship training and high annual volume of cases are associated with lower rates of injury 20–22 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Increasingly, reconstructive and POP procedures are being performed by high-volume surgeons in general and those fellowship trained in female pelvic medicine and reconstructive surgery, with the former reflected in this cohort, where more than 75% of cases were performed by surgeons who perform more than 50 surgical procedures for POP per year 17–19 . Previous studies have suggested that both fellowship training and high annual volume of cases are associated with lower rates of injury 20–22 .…”
Section: Discussionmentioning
confidence: 87%
“…Increasingly, reconstructive and POP procedures are being performed by high-volume surgeons in general and those fellowship trained in female pelvic medicine and reconstructive surgery, with the former reflected in this cohort, where more than 75% of cases were performed by surgeons who perform more than 50 surgical procedures for POP per year. [17][18][19] Previous studies have suggested that both fellowship training and high annual volume of cases are associated with lower rates of injury. [20][21][22] Although we were not able to determine which health care providers were fellowship trained, we did find that surgical procedures performed by surgeons with fewer than 50 POP surgical procedures per year were more likely to be associated with GUTI, particularly if the surgical volume was fewer than 12 per year.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are frequently concerned about the impact of surgical trainees and the negative impact they may have on their surgery. Carter-Brooks et al, performed a retrospective review of 208 RSC and noted that although fellows took about 30 minutes longer, there was no impact on the overall complication or recurrence rates as compared to cases without fellows (46). In addition, Crane et al, noted that although total robot docked times were longer for trainees (23 minutes), the overall average hysterectomy and sacrocolpopexy times were not different when trainees were involved in patient care (47).…”
Section: Ancillary Factors Impacting Efficacymentioning
confidence: 99%